Inkjet-Printed CdTe Quantum Dots-Polyurethane Acrylate Thin Films. (2nd November 2017) - Du, Lei; Liu, Zhejun; Jiang, Suhua
Abstract : We demonstrated the inkjet-printed CdTe quantum dots-polyurethane acrylate thin films and their potential application in the display devices. The water soluble CdTe QDs were synthesized through the wet chemistry and the emission wavelengths can be freely tuned during the preparation process. Combining with the UV curable resin polyurethane acrylate, the QDs inks were prepared and the influence of diluent and water content on the performance of resultant films was studied. The tensile stress of the films cured from the QDs inks with diluent increased from 10.6 MPa to 27.5 MPa and the low water content led to uniform polymer matrix. Furthermore, the existence of diluent and low water content would all improve the fluorescence stability of the thin films. Finally, the thin films can be deposited on different substrates and well controlled to meet the RGB color standard, which will pave the way to a simple, low-cost, large-scale, and highly reliable method for the application of flexible displays.